Brown bear, brown bear, what do you see? - Martin, Bill 1916-; Carle, Eric. (New York Henry Holt and Company, 1992)
Children see a variety of animals, each one a different color, and a teacher looking at them.
First published in 1967 in a slightly different form by the School Division, Holt, Rinehart and Winston.
Keywords: Colors -- Juvenile poetry; Animals -- Juvenile poetry